Spiritual Mindfulness Effect on Anxiety, Respiratory Rate and Oxygen Saturation in Pneumonia Patients - Diah Priyantini; Daviq Ayatulloh; Dimas Hadi Prayoga (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pneumonia in addition to causing problems in the respiratory system, also causes psychological disorders, manifesting as anxiety, causing worry, instilling feelings of restlessness, and triggering constant fear that has implications for daily functioning. Supportive therapy is needed to provide a good impact on the respiratory system and patient anxiety. The purpose of this study was to analyze the effect of spiritual mindfulness on anxiety, respiratory rate and oxygen saturation of pneumonia patients. Quantitative research with a quasi-experimental approach (pre-post test with control group design) in one of the hospitals in Gresik Regency. The sample in the study consisted of 64 divided into intervention groups and control groups recruited using purposive sampling. The independent variable is spiritual mindfulness with a frequency of 3 days and an intensity of 15 minutes. The research instrument to measure anxiety used a questionnaire from Zung SARS, respiratory rate was measured using direct observation for 1 minute and oxygen saturation was measured by observation through pulse oximetry. The analysis used in the study used the paired T-Test and the Wilcoxon signed rank test with a significance level of α ≤ 0.05. Spiritual mindfulness intervention showed a significant effect on respiratory rate (p=0.000), oxygen saturation (p=0.000) and anxiety (p=0.000) in the intervention group, but in the control group all showed no significant effect. The results of the calculation of the effect size of respiratory rate showed a value of d = 1.059, oxygen saturation showed a value of d = 0.735 and anxiety showed a value of d = 1.436. Spiritual mindfulness showed effectiveness in reducing anxiety levels, reducing respiratory rate and increasing oxygen saturation in pneumonia patients.